2021
DOI: 10.21203/rs.3.rs-921538/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contribution of Low Birth Weight to Childhood Malnutrition in India

Abstract: Background Although Low birth weight (LBW) is an independent predictor of malnutrition, it is still a negligible public health issue in the Indian context. Where, a large number of children died due to complications from maternal and child malnutrition. Furthermore, each year, India loses its GDP due to the cost of micronutrient malnutrition which is more that the public health budget. MethodsTo conduct the study, 4th round of the National Family Health Survey (NFHS-4), a large-scale survey was used. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Previous studies based on data from Bangladesh showed that LBW was identified as an important risk factor for various forms of undernutrition [26,27]. Several neighboring countries like India, and Pakistan found comparable results [50,51]. Another study in Africa (Malawi) also found higher odds of stunting, wasting, and being underweight among LBW children [52].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies based on data from Bangladesh showed that LBW was identified as an important risk factor for various forms of undernutrition [26,27]. Several neighboring countries like India, and Pakistan found comparable results [50,51]. Another study in Africa (Malawi) also found higher odds of stunting, wasting, and being underweight among LBW children [52].…”
Section: Discussionmentioning
confidence: 95%
“…Another study in Africa (Malawi) also found higher odds of stunting, wasting, and being underweight among LBW children [52]. LBW infants often had difficulties in feeding due to underdeveloped digestive systems or a weak sucking reflex, which can lead to inadequate intake of nutrients [50,53]. Moreover, LBW infants may have higher metabolic rates, which means they require more energy and nutrients per kilogram of body weight than a normal infant and this supply-demand imbalance leads to undernourishment [54].…”
Section: Discussionmentioning
confidence: 99%